A Clinicopathological Study of Solitary Thyroid Nodule - Haque, GHM Shahidul; Hossain, Md Jakir; Haque, Sabrina; Rahman, Md Anisur (Medicine Today, 2019)
Introduction:Common presentation of thyroid disorders is solitary nodule. A discrete swelling in an otherwise impalpable gland is termed as solitary nodule of thyroid. The majority of solitary thyroid nodules are benign. The incidence of malignancy is 10-20%, being more common in females with a mean age of 35 years.The object of the study was to identify the incidence of malignancy in solitary nodule thyroid which emphasizes on the early diagnosis and adequate treatment. Materials and Methods: The study was carried out in the department of ENT and Head-Neck Surgery of Rangpur Medical College Hospital, Rangpur and Shaheed Ziaur Rahman Medical College Hospital, Boruga in 50 patients with solitary thyroid nodule from July 2013 to June 2015. Results: The solitary thyroid nodules were seen in 1.76% of surgical admissions. The mean age of the incidence of solitary thyroid nodule is 35 years. The incidence of malignancy in solitary thyroid nodule is 18.51%. The solitary thyroid nodules were frequent in females than males in the ratio of 6.71:1. Conclusion: It is concluded from the present study that a remarkable proportion 10% of solitary thyroid nodules was malignant with females preponderance which emphasizes on the early diagnosis and adequate treatment. Medicine Today 2019 Vol.31(2): 85-88